The stool microbiota and infant wheezing illness - the Drakenstein child health study, South Africa - Ngwarai, Michelle Rudo (Department of Pathology, 2020)
Background: Wheezing is one of the leading respiratory symptoms in childhood, which with recurrent occurrence can lead to asthma at school age. Few studies, with conflicting findings, have investigated the contribution of stool bacteria in childhood wheezing illness. Additionally, most of the published studies were conducted in high-income countries using small sample sizes and targeted bacterial detection techniques. To address these limitations, we conducted this study to determine the association of the infant stool bacterial diversity and composition with wheezing development. Methods: We conducted a longitudinal case-control study nested within the Drakenstein Child Health Study, Western Cape, South Africa. We included 140 infants with wheeze (cases) and 140 age-matched controls. Passed faecal samples were collected from infants at birth, whilst aspirated or passed faecal samples were collected at six weeks, six months and 12 months. Deoxyribonucleic acid (DNA) was extracted from all the samples using the manual ZR Fecal DNA MiniPrep™ Kit. Sequencing of the hypervariable V4 region of the 16S rRNA gene was performed using the Illumina MiSeq technique. The resulting sequencing data was subjected to bioinformatic quality control checks and statistical analysis. Results: One of the main findings from the systematic review of wheezing data was the observed association between the development of atopic wheezing and four bacteria namely Faecalibacterium, Lachnospira, Veillonella and Rothia. This study included 280 children (n=123 female and n=157 male) recruited from TC Newman (38.5%) and Mbekweni (61.5%) areas. Stool samples were collected from 159 infants at birth, 114 infants at six weeks, 141 infants at six months and 98 infants at 12 months of age. Aspirate and passed stool samples were found to be similar and comparable in terms of the bacterial composition. At age six weeks, 16% (23/140) of the infants included had wheezed once. During the first year, the proportion of infants with recurrent wheezing (≥ 2 wheezing episodes) was 56% (78/140). Independent factors influencing the composition and diversity of the infants faecal bacteria were feeding practices, age of mothers and living conditions (all p0.05). In addition, we did not find significant difference between infants with and without wheeze for selected bacteria reported to be associated with wheezing. However, we observed an increased relative abundance of Proteobacteria at 12 months of age in infants who had previously wheezed. Additionally, Lactobacillales was in apparently significantly higher proportions in recurrent wheezers as compared to infants who wheezed once (p< 0.05). We did not observe distinct faecal bacterial profiles between infants with and without wheeze at any taxonomic level analysis (all p> 0.05). In addition, we did not find significant difference between infants with and without wheeze for selected bacteria reported to be associated with wheezing. However, we observed an increased relative abundance of Proteobacteria at 12 months of age in infants who had previously wheezed. Additionally, Lactobacillales was in apparently significantly higher proportions in recurrent wheezers as compared to infants who wheezed once (p< 0.05). Conclusion: This study shows that aspirated stool is a good alternative for passed stool in microbiome studies. Furthermore, it revealed the complex and dynamic nature of the faecal bacteria, as well as factors influencing the faecal bacterial profile during the first year of life. More studies in this cohort, including the use of metagenomic and metabolomic approaches are required to demonstrate the role played by bacterial types and their metabolites in the development of wheezing illness. Finally, because recurrent wheezing is one of the precursors of asthma, there is a need for an additional follow-up of these infants in order to investigate the contribution of the early faecal microbiome in the development of asthma at school age.